2000
DOI: 10.1029/2000gl003744
|View full text |Cite
|
Sign up to set email alerts
|

Terdiurnal oscillations in OH Meinel rotational temperatures for fall conditions at northern mid‐latitude sites

Abstract: Abstract. High-precision (4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 16 publications
2
54
0
Order By: Relevance
“…sion it has been found to be comparable (Teitelbaum et al, 1989;Thayaparan, 1997;Taylor et al, 1999;Pendleton et al, 2000;Namboothiri et al, 2004). The terdiurnal tide has also been found to be characterized by significant amplitudes (wind speeds over 20 m s −1 and temperature over 15 K) in the lower thermosphere (90-100 km).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…sion it has been found to be comparable (Teitelbaum et al, 1989;Thayaparan, 1997;Taylor et al, 1999;Pendleton et al, 2000;Namboothiri et al, 2004). The terdiurnal tide has also been found to be characterized by significant amplitudes (wind speeds over 20 m s −1 and temperature over 15 K) in the lower thermosphere (90-100 km).…”
Section: Introductionmentioning
confidence: 72%
“…The diurnal and semidiurnal tides are the most prominent tidal components found in the MLT, but the terdiurnal (8-h) tidal component has been also seen in a number of observations of the MLT (Teitelbaum et al, 1989;Thayaparan, 1997;Taylor et al, 1999;Pendleton et al, 2000;Smith, 2000;Akmaev, 2001;Yi, 2001;Aso, 2003;Batista et al, 2004;Namboothiri et al, 2004;Zhang et al, 2004;Wu et al, 2005), indicating that it is a permanent feature of the horizontal wind and temperature variability there. The amplitude of the terdiurnal tide is generally smaller than that of the diurnal or semidiurnal tide, although on occaCopyright c The Society of Geomagnetism and Earth, Planetary and Space Sciences (SGEPSS); The Seismological Society of Japan; The Volcanological Society of Japan; The Geodetic Society of Japan; The Japanese Society for Planetary Sciences; TERRAPUB.…”
Section: Introductionmentioning
confidence: 99%
“…The high quantum efficiency (∼50% at near-infrared wavelengths) and low noise characteristics (dark current ∼0.1 e − /pixel/s at −50 • C) of the CCD array provide an exceptional capability of high quality nocturnal measurements of OH and O 2 emission intensity (<0.5% in 1 min) and derived rotational temperatures (precision <1-2 K in 3 min). The details of this instrument are discussed elsewhere (Pendleton et al, 2000;Taylor et al, 2001). …”
Section: Instrument and Observationsmentioning
confidence: 99%
“…Nevertheless, the 8-h tide, as a distinct wave signature in the MLT region, is not well understood, especially compared to the diurnal tide and semidiurnal tide. Besides the work of Smith (2000) based on the wind measurement of High Resolution Doppler Interferometer (HRDI) instrument on the Upper Atmosphere Research Satellite (UARS), the variations of the 8-h tide have been investigated using ground-based observations in the Northern Hemisphere at middle-and high-latitude (Manson and Meek, 1986;Teitelbaum et al, 1989;Thayaparan, 1997;Pendleton et al, 2000;Younger et al, 2002;Namboothiri et al, 2004;Taori et al, 2005;Zhao et al, 2005;Beldon et al, 2006). These studies showed that the seasonal behavior of the 8-h tide in the MLT region is different at different latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The features and seasonal variabilities of the diurnal tide and semidiurnal tide in the mesosphere and lower thermosphere (MLT) have been quite well investigated through observations and model simulations (Manson and Meek, 1986;Teitelbaum et al, 1989;Thayaparan, 1997;Pendleton et al, 2000;Smith, 2000;Smith and Ortland, 2001;Akmaev, 2001;Younger et al, 2002;Batista et al, 2004;Namboothiri et Correspondence to: G. Jiang (gyjiang@spaceweather.ac.cn) al., 2004;Taori et al, 2005;Zhao et al, 2005;Beldon et al, 2006;Tokumoto et al, 2007). Nevertheless, the 8-h tide, as a distinct wave signature in the MLT region, is not well understood, especially compared to the diurnal tide and semidiurnal tide.…”
Section: Introductionmentioning
confidence: 99%